2017
DOI: 10.1063/1.4999358
|View full text |Cite
|
Sign up to set email alerts
|

Practical methods for generating alternating magnetic fields for biomedical research

Abstract: Alternating magnetic fields (AMFs) cause magnetic nanoparticles (MNPs) to dissipate heat while leaving surrounding tissue unharmed, a mechanism that serves as the basis for a variety of emerging biomedical technologies. Unfortunately, the challenges and costs of developing experimental setups commonly used to produce AMFs with suitable field amplitudes and frequencies present a barrier to researchers. This paper first presents a simple, cost-effective, and robust alternative for small AMF working volumes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…4F), consistent with the biochemical inertness of iron oxides (30). In the postmortem analysis of the adrenal tissue injected with NPs, we found that 80% of the rats harbored injection sites in the adrenal medulla, 90% had injection sites in the ZF and zona reticularis, and only 25% had injection sites in the zona glomerulosa (n = 12; To deliver AMF conditions sufficient to drive hysteretic heat dissipation in MNPs injected in adrenal glands, we used a custom apparatus (28), capable of producing AMFs with amplitudes up to H = 13.5 ± 1.5 kA/m at a frequency ƒ = 557 kHz (SLP = 620 ± 190 W/g) across a volume of ~200 cm 3 , which accommodates an adult Long-Evans rat (Fig. 5, C and D, and fig.…”
Section: Remote Control Of Adrenal Hormone Releasementioning
confidence: 61%
See 1 more Smart Citation
“…4F), consistent with the biochemical inertness of iron oxides (30). In the postmortem analysis of the adrenal tissue injected with NPs, we found that 80% of the rats harbored injection sites in the adrenal medulla, 90% had injection sites in the ZF and zona reticularis, and only 25% had injection sites in the zona glomerulosa (n = 12; To deliver AMF conditions sufficient to drive hysteretic heat dissipation in MNPs injected in adrenal glands, we used a custom apparatus (28), capable of producing AMFs with amplitudes up to H = 13.5 ± 1.5 kA/m at a frequency ƒ = 557 kHz (SLP = 620 ± 190 W/g) across a volume of ~200 cm 3 , which accommodates an adult Long-Evans rat (Fig. 5, C and D, and fig.…”
Section: Remote Control Of Adrenal Hormone Releasementioning
confidence: 61%
“…Magnetothermal adrenal actuation with an externally applied AMF (15 kA/m, 515 kHz) generated in a custom coil driven by a resonant circuit (28) was observed in 50% of the examined cells (n = 140) in the presence of MNP solutions (5 mg/ml) ( Fig. 3, H to J, and fig.…”
Section: Calcium Influx In Adrenal Cell Culturementioning
confidence: 96%
“…For the second experiment, we imaged a new FOV on the same coverslip during stimulation by a magnet or sham magnet. [10][11][12][13][14][15][16][17][18][19][20] FOVs from independent cell cultures were recorded for each condition, yielding R1000 cells per condition. When calculating statistical significance, we considered both individual cells ( Fig.…”
Section: Magnetic Stimulation Of the Channel Magneto20 Under Differementioning
confidence: 99%
“…Although exogenous chemically synthesized nanoparticles can effectively create magnetically sensitive cells, a method that did not require delivery of synthetic nanoparticles and relied on low-frequency magnetic fields would have a number of advantages. Generating high-frequency AMFs of sufficient amplitude to stimulate cells in vivo requires magnetic field generators that cost thousands of dollars and consume 5-15 kW of power (12). Low-frequency magnetic field generation consumes much less power and can even be achieved using a permanent magnet.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this approach has a number of disadvantages. High-frequency AC fields -up to ∼ 0.5 MHz -with intensities of O(0.1 T) can only be produced within bore volumes of a few cm 3 [22][23][24][25]. Furthermore, solenoids that produce such high frequencies and field intensities require strong currents and thick, tightly winded coils that would generally experience significant ohmic losses.…”
Section: Detection Sensitivitymentioning
confidence: 99%